1994
DOI: 10.1021/bi00192a004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the Binary Ca2+ and pdTp Complexes and the Ternary Complex of the Asp21 .fwdarw. Glu Mutant of Staphylococcal Nuclease. Implications for Catalysis and Ligand Binding

Abstract: The crystal structure of the Asp21-->Glu mutant (D21E) of staphylococcal nuclease (SNase) has been determined in three different complex forms. The structure of the D21E ternary complex in which D21E is bound to both Ca2+ and the transition-state analogue, thymidine 3',5'-diphosphate (pdTp), was determined to 1.95-A resolution. The structures of both binary complexes, D21E bound either to Ca2+ or pdTp, were determined to 2.15- and 2.05-A resolution, respectively. In the ternary structure, we find a 1.5-A movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Other substantial changes in coordination of calcium occur, including a change in the number of coordinating water molecules and new ligation by glutamate 43, which is not coordinating in the wild-type protein. In addition, more long-range alterations in protein structure are also observed (46). This work provides a precedent for the interpretation of our vibrational spectra.…”
Section: Interpretation Of the Lines In The 1750 To 1670 CMsupporting
confidence: 56%
See 2 more Smart Citations
“…Other substantial changes in coordination of calcium occur, including a change in the number of coordinating water molecules and new ligation by glutamate 43, which is not coordinating in the wild-type protein. In addition, more long-range alterations in protein structure are also observed (46). This work provides a precedent for the interpretation of our vibrational spectra.…”
Section: Interpretation Of the Lines In The 1750 To 1670 CMsupporting
confidence: 56%
“…A change in inner-sphere coordination of a metal is also observed when an aspartate-to-glutamate mutation is introduced at a Ca 2ϩ ligand in staphylococcal nuclease (46). In this case, the substitution of glutamate for aspartate 21 results in a change from unidentate ligation by aspartate 21 to bidentate ligation by glutamate 21.…”
Section: Interpretation Of the Lines In The 1750 To 1670 CMmentioning
confidence: 98%
See 1 more Smart Citation
“…Through the crystal structure at 1.95 A î resolution of the D21E ternary complex, where D21E is bound to both Ca 2 and pdTp (transition state analogue), it was demonstrated that Ca 2 in the active site binds to Glu21 via bidentate coordination and to Glu43 through an inner sphere coordination. The cooperativity of the metal ion and the inhibitor (pdTp) in the ternary complex was also demonstrated [187].…”
Section: Coordination and Function Of Metal Ionsmentioning
confidence: 94%
“…inally proposed Glu-43 as acting as a general base in the reaction mechanism, yet more recent evidence (Wang et al, 1990;Judice et al, 1993;Libson et al, 1994) indicates otherwise. Clearly the catalytic mechanism for this enzyme is more complex than previously proposed Loll & Lattman, 1989), particularly given the requirement of not one but two equivalents of Ca2+ for maximal activity (Cuatrecasas et al, 1967b;Tucker et al, 1979a, Tucker et al, 1979b.…”
mentioning
confidence: 99%